Inverse Association Between Metabolic Syndrome and Altitude: A Cross-Sectional Study in an Adult Population of Ecuador - Lopez-Pascual, Amaya; Arévalo, Jéssica; Martínez, J. Alfredo; González-Muniesa, Pedro (Frontiers in Endocrinology, 2018)
Background: Metabolic syndrome (MetS) is characterized by the clustering of hyperglycemia, hypertension, hypertriglyceridemia, low high-density lipoprotein cholesterol levels and central adiposity. Altitude has been proposed as a protective factor to prevent the development of MetS and its components. Aim: To determine whether living at geographical elevation is associated with MetS and its individual components after adjustment for potential confounders in an Ecuadoran population. Methods: The study included 260 Ecuadoran university graduates over 20 years of age, from the coastal or the Andean Altiplano region. The altitude of residence was imputed with the postal code of each participant residence according to the data of the Ecuadoran Geophysical Institute of the National Polytechnic School. MetS was defined according to the harmonizing definition. Logistic regression models were fitted to assess the relationship between altitude level and the prevalence of MetS and its individual components. To test the internal validity, re-sampling techniques were used (1,000 bootstrap samples). Results: Living at high altitude was associated with less hypercholesterolemia (OR = 0.24; p <0.001), hyperglycemia (OR = 0.25; p <0.05) and MetS (OR = 0.24; p <0.05), after adjusting for potential confounders. At high altitude the bootstrapped logistic regression models showed lower prevalence of hypercholesterolemia (OR = 0.30; p <0.05), hyperglycemia (OR = 0.22; p <0.001) and MetS (OR = 0.28; p <0.05). The MetS score (0-5 points) showed a reduction in the number of MetS components at high altitude compared to sea level (β = -0.34; p = 0.002). A statistically significant lower self-reported energy intake was found in high altitude compared to sea level after adjustment for potential confounders (p <0.001). Conclusion: In the present study concerning a small Ecuadoran population composed of highly educated adults living at the coast and the Andean Altiplano, living at high altitude (2,758-2,787 m) was associated with a lower prevalence of MetS, hypercholesterolemia and hyperglycemia, compared to the participants at sea level (4-6 m). In addition, an inverse association between altitude and self-reported energy intake was found after adjusting for covariates, suggesting a physiological role of appetite at high altitude even in acclimated subjects.